Association Between Daily Sleep Duration and Risk of Dementia and Mortality in a Japanese Community. Issue 10 (6th June 2018) - Ohara, Tomoyuki; Honda, Takanori; Hata, Jun; Yoshida, Daigo; Mukai, Naoko; Hirakawa, Yoichiro; Shibata, Mao; Kishimoto, Hiro; Kitazono, Takanari; Kanba, Shigenobu; Ninomiya, Toshiharu
Abstract : Objectives: To investigate the association between daily sleep duration and risk of dementia and death in a Japanese elderly population. Design: Prospective cohort study. Setting: The Hisayama Study, Japan. Participants: Community‐dwelling Japanese individuals aged 60 and older without dementia. Measurements: Self‐reported daily sleep duration was grouped into 5 categories (<5.0, 5.0–6.9, 7.0–7.9, 8.0–9.9, ≥10.0 hours). The association between daily sleep duration and risk of dementia and death was determined using a Cox proportional hazards models. Results: During follow‐up, 294 participants developed dementia, and 282 died. Age‐ and sex‐adjusted incidence rates of dementia and all‐cause mortality were significantly greater in subjects with daily sleep duration of less than 5.0 hours and 10.0 hours and more than in those with daily sleep duration of 5.0 to 6.9 hours. These associations remained unchanged after adjustment for potential confounding factors (<5.0 hours: hazard ratio (HR)=2.64, 95% confidence interval (CI)=1.38–5.05 for dementia; HR=2.29, 95% CI=1.15–4.56 for death; ≥10.0 hours: HR=2.23, 95% CI=1.42–3.49 for dementia; HR=1.67, 95% CI=1.07–2.60 for death). Similar U‐shaped associations were observed for Alzheimer's disease and vascular dementia. With regard to the influence of hypnotic use on risk of dementia and death, subjects who used hypnotics and had any sleep duration had a risk of dementia that was 1.66 times as great and a risk of death that was 1.83 times as great as those who did not use hypnotics and had a daily sleep duration of 5.0 to 6.9 hours. Conclusion: Short and long daily sleep duration and hypnotic use are risk factors for dementia and death in Japanese elderly adults.